(h+9)=2(h+9)+-6

Simple and best practice solution for (h+9)=2(h+9)+-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (h+9)=2(h+9)+-6 equation:


Simplifying
(h + 9) = 2(h + 9) + -6

Reorder the terms:
(9 + h) = 2(h + 9) + -6

Remove parenthesis around (9 + h)
9 + h = 2(h + 9) + -6

Reorder the terms:
9 + h = 2(9 + h) + -6
9 + h = (9 * 2 + h * 2) + -6
9 + h = (18 + 2h) + -6

Reorder the terms:
9 + h = 18 + -6 + 2h

Combine like terms: 18 + -6 = 12
9 + h = 12 + 2h

Solving
9 + h = 12 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
9 + h + -2h = 12 + 2h + -2h

Combine like terms: h + -2h = -1h
9 + -1h = 12 + 2h + -2h

Combine like terms: 2h + -2h = 0
9 + -1h = 12 + 0
9 + -1h = 12

Add '-9' to each side of the equation.
9 + -9 + -1h = 12 + -9

Combine like terms: 9 + -9 = 0
0 + -1h = 12 + -9
-1h = 12 + -9

Combine like terms: 12 + -9 = 3
-1h = 3

Divide each side by '-1'.
h = -3

Simplifying
h = -3

See similar equations:

| 2(x-3)+x+4=9-2x+1+x | | M^2+7m+p^2=0 | | y(h+9)=2(h+9)+-6 | | 2x-34=20 | | 2t^3+t-3=0 | | m+m+9=3+m | | 21=-5k | | M^2+7m=p^2 | | 20x-5+17-3x= | | 21=-5+k | | 70+70+w*2=340 | | 5x+3-37=6x+23-8x | | -4x+-2.363636364=-2 | | 12=44x-12 | | 0.5+0.25y-3y=7 | | 0.5cos(x)=sin(2x) | | Y=1.1x^2+4.2x+4.9 | | 2x^2+x=69 | | y-4.5=12.2 | | x^2+(y-5)=30 | | 4x^2(-5+-15x+x^2+3x^3)= | | 8.1=a-(-2.4) | | 0.3x^2-2x+3.6=0 | | -5x+7=-8+9x | | 42u=4.66666666667 | | -6x-3=4x+7 | | 50=10x+15-3x | | g+-7=21 | | 2x(3)-18x=0 | | (3x+6)(2x-5)=0 | | y=15x-5 | | 4(1.5+0.25y)-y=6 |

Equations solver categories